Challenging the status quo of an institutional culture in theological training - Naidoo, Marilyn (Stellenbosch Theological Journal, 2017)
Institutional culture is one of the most salient forces operating in higher education because it is a vehicle for implementing organizational and institutional change. This article reports on an ethnographic study that focused on the role of a theological institution’s culture and how the culture shaped diversity management, and ultimately student formation. This article highlights the saliency of the institutional culture in maintaining the status quo and not supporting the establishment of more equitable learning environments. Within theological education we need to dismantle beliefs and practices that shape and sustain social injustice and that will require some institution cultures to be challenged and changed. Being aware of the formative nature of the institutional culture provides critical insights into an institution’s change process and can help theological students and educators to find a common theological discourse.